Fuel Used Analysis on Boiler Efficiency Variations and Water Intake Temperature Affected by Palm Oil Varieties - Zulham Effendi; Siti Aisyah; Rionaldo Hastyanda (Universitas Panji Sakti, 2021)
Several factors that affect the use of fuel in boilers are combustion efficiency, quality of feed water management, calorific value, and the potential for available fuel from oil palm varieties. The purpose of this research is to identify the use of fuel and its potential savings based on variations in boiler efficiency and water temperature that entered the boiler. The materials used in this research are FFB mass balance data and boiler fuel composition. Based on the analysis results, the lowest used fuel mass and the highest fuel savings are found in the DxPLangkat variety with an intake water temperature of 105o C and 80% boiler efficiency. The use of fuel is 4,231 kg/hour with shell savings of 967 kg/hour with a value of IDR 725,701. Fiber savings was 487 kg/hour with a value of IDR 121,751.The highest used fuel mass and the lowest fuel savings were found in the Yangambi derivative variety with an intake water temperature of 85o C and 60% boiler efficiency.The fuel consumption is 5,830 kg/hour with shell savings totalling -380 kg/hour. There is no fiber analysis because it is used up hence additional fuel is needed. Additional fuel can be done by asking for other palm oil mill units or buying. If they buy a shell with a requirement of 380 kg/hour, the funds required are IDR 284,939.